2023
DOI: 10.1002/ccd.30603
|View full text |Cite
|
Sign up to set email alerts
|

Cutting balloon to optimize predilation for stent implantation: The COPS randomized trial

Abstract: Objectives: The objective of this study is to investigate the use of cutting balloon (CB) inflated at high pressure compared with noncompliant balloon (NCB) for the treatment of calcified coronary lesions.Background: No data are available regarding the safety and efficacy of CB inflated at high pressure in coronary artery calcifications.Methods: Patients with calcified lesions (more than 100°of calcium demonstrated at baseline intravascular ultrasound) were randomized. Primary endpoint of the study was the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…21 Moreover, in the COPS study no significant difference in MSA was observed between lesions treated with cutting balloons as compared with noncompliant balloons, although the trial did show a significant difference in MSA at the calcium site. 22 In line with the subanalysis on specialty devices in the present study, the small sample size of both studies should be acknowledged and a clear trend toward better stent expansion with more aggressive lesion preparation was consistently observed. Adequately powered randomized trials will be needed to demonstrate the potential superiority of these lesion preparation techniques as compared with routine noncompliant balloons.…”
Section: Discussionsupporting
confidence: 80%
“…21 Moreover, in the COPS study no significant difference in MSA was observed between lesions treated with cutting balloons as compared with noncompliant balloons, although the trial did show a significant difference in MSA at the calcium site. 22 In line with the subanalysis on specialty devices in the present study, the small sample size of both studies should be acknowledged and a clear trend toward better stent expansion with more aggressive lesion preparation was consistently observed. Adequately powered randomized trials will be needed to demonstrate the potential superiority of these lesion preparation techniques as compared with routine noncompliant balloons.…”
Section: Discussionsupporting
confidence: 80%
“…In an early randomized study of 521 patients undergoing cutting balloon angioplasty or conventional balloon angioplasty before IVUS-guided stenting, the patients undergoing cutting balloon angioplasty had a larger minimal lumen area and lower rate of restenosis ( 55 ). This has been recently replicated in the COPS study ( 56 ).…”
Section: Balloon-based Techniquesmentioning
confidence: 65%
“…In this issue of Catheterization Cardiovascular Interventions , Mangieri et al 2 present the results of a multicenter randomized controlled trial comparing a new high‐pressure CB angioplasty protocol with high‐pressure noncompliant balloon (NCB) angioplasty. Their Cutting balloon to Optimize Predilatation for Stent implantation (COP) study included 100 patients with >100° of calcification under IVUS and a reference vessel diameter of 2.5–4.0 mm.…”
Section: Figurementioning
confidence: 99%
“…In this issue of Catheterization Cardiovascular Interventions, Mangieri et al 2 present the results of a multicenter randomized controlled trial comparing a new high-pressure CB angioplasty protocol with high-pressure noncompliant balloon (NCB) angioplasty.…”
mentioning
confidence: 99%